Blood parasites of village goats in southwest Nigeria - Opasina, B.A. (1984)
Blood screening over 12 months in 4 groups of villages in southwest Nigeria revealed the prevalence of Trypanosoma vivax (3.5%) and Babesia motasi (20.4%). There was a very high infection rate from B.motasi, although clinical babesiosis was not common. Although infection from T.vivax and B.motasi occurred at all seasons, the peaks of infection were observed in the rainy season. Infection from T.vivax appeared to be clinical in nature, and was very much associated with low packed cell volume (PCV). Infection from Anaplasma spp. was very low. Although infection by blood parasites among village goats has been considered low grade, the effects on the productivity of the animals would need to be ascertained.